1999
DOI: 10.1124/mol.56.3.570
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Nucleotide Analogs Cidofovir and Adefovir Are Novel Substrates for Human and Rat Renal Organic Anion Transporter 1

Abstract: Nephrotoxicity is the dose-limiting clinical adverse effect of cidofovir and adefovir, two potent antiviral therapeutics. Because renal uptake likely plays a role in the etiology of cidofovir- and adefovir-associated nephrotoxicity, we attempted to identify a renal transporter capable of interacting with these therapeutics. A cDNA clone was isolated from a human renal library and designated human organic anion transporter 1 (hOAT1). Northern analysis detected a specific 2.5-kilobase pair hOAT1 transcript only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
258
3
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(275 citation statements)
references
References 34 publications
(48 reference statements)
11
258
3
3
Order By: Relevance
“…This later proved to be true, but only in part, as several other transporters are now known to be involved. Soon after rOat1 had been cloned, other Oat1 orthologs were identified; in human, pig, rabbit, mouse, flounder and C. elegans [43][44][45][46][47][48][49][50][51]. To date, Oat1 message has been detected in kidney, choroid plexus and olfactory mucosa [52][53][54].…”
Section: The Organic Anion Transporter Familymentioning
confidence: 99%
“…This later proved to be true, but only in part, as several other transporters are now known to be involved. Soon after rOat1 had been cloned, other Oat1 orthologs were identified; in human, pig, rabbit, mouse, flounder and C. elegans [43][44][45][46][47][48][49][50][51]. To date, Oat1 message has been detected in kidney, choroid plexus and olfactory mucosa [52][53][54].…”
Section: The Organic Anion Transporter Familymentioning
confidence: 99%
“…The basolateral exchanger for organic anions and dicarboxylates was cloned by three independent groups (5-7) in 1997 and named OAT1 (rat), ROAT1 (rat), or fROAT1 (winter flounder). The homologous protein was cloned from human kidney only recently and was called hOAT1 (8) or hPAHT (9,10). The genomic DNA from human hOAT1 is organized in ten exons, and up to now four isoforms are described (11).…”
mentioning
confidence: 99%
“…As toxins and cytotoxic drugs are taken up by OAT1 and OAT3, these toxic substances may exert toxic effects on the proximal tubule cells and cause renal injury. In vitro studies with OAT1-transfected cells showed that OAT1 over-expression sensitizes the cytotoxicity caused by antiviral drugs, adefovir and cidofovir [23]. Coadministration of the inhibitors of OATs may reduce the extent of OAT-induced nephrotoxicity [24].…”
Section: Introductionmentioning
confidence: 99%